(X-2 / 5-x-2) / 3x-6 / 3-x is calculated (X-5 / 2) - X-2) / (3x-6 / 3-x)

(X-2 / 5-x-2) / 3x-6 / 3-x is calculated (X-5 / 2) - X-2) / (3x-6 / 3-x)

=X-2 / 3-x) / 3-x / 3 X-6 3-x about 3x-6 = 3 (X-2) X-2 about 3x-6
=3

54 + 4x = 75 + X how much is x? Use equation

54+4X=75+X
4x-x = 75-54
3x=21
x=7
Potato troupe Shao Wenchao answers your questions
If you don't understand this question, you can ask,

Calculation: X * x + 4x = 2, how much is x

x ²+ 4x=2
x ²+ 4x+4=6
(x+2) ²= six
x+2=±√6
x1=√6-2, x2=-√6-2

Calculation: x ^ 2-9 / 4-x ^ 2 * x ^ 2 + X-2 / x ^ 2-4x + 3,

(x^2-9)/(4-x^2) * (x^2+x-2)/(x^2-4x+3)
=(x-3)(x+3)/(2-x)(2+x) * (x+2)(x-1)/[(x-1)(x-3)]
=(x+3)/(2-x)

The positive integer solution of inequality group 2 (X-6) less than 3-x, (2x-1) / 3 - (5x + 1) / 2 less than or equal to 1 is ()

2x-12

Find inequality 3 (x − 1) 2)   Maximum integer solution of ≤ 2 (x − 3) + 1

Solving inequality 3 (x − 1)
2)   ≤2(x−3)+1
De bracketed: 3x-3
2≤2x-6+1
Displacement: 3x-2x ≤ 3
2-6+1
Then x ≤ - 7
two
The maximum integer is - 4